Temporal trends in the characteristics, treatment and clinical outcomes of conservatively managed patients with non-ST elevation acute coronary syndrome: ACSIS registry 2000–2016. (14th October 2021) - Aviv, Y; Shechter, A; Richter, I; Kornowski, R; Ovdat, T; Pereg, D; Eisen, A
Abstract: Background: Despite advances in percutaneous coronary interventions (PCI), a sub group of acute coronary syndrome (ACS) patients are still managed medically by a conservative approach. We sought to characterize a contemporary, large-scale, real-world cohort of ACS patients treated conservatively via pharmacological management, without PCI. Methods: Data from the ACS Israeli Survey (ACSIS) accrued between 2000–2016, encompassing all consecutive patients admitted to cardiology wards with an ACS diagnosis. Examined were 3543 conservatively managed patients with non-ST elevation ACS (NSTE-ACS). Patients with ST elevation MI or those referred to bypass surgery were excluded. Primary endpoints were 30-day major adverse cardiovascular events (MACE) and 1-year mortality. The study cohort was divided to 4 time-periods. Results: Over 2 decades, medically managed NSTE-ACS patients remained of similar age (67±13y, p=0.78), but had more atherosclerotic risk-factors and comorbidities. During time, patients were more often referred to diagnostic angiography and treated with statins, ACE-I/ARBs, and P2Y12 inhibitors (p<0.001 for each). Over time, there were less in-hospital complications such as kidney injury and heart failure. The rate of 30-day MACE decreased (from 20.7% to 10.3%, earliest to latest period, p<0.001). Compared with the earliest period, the latest period was associated with a reduction in 1-year mortality (14.7% to 11.6%; adjusted HR 0.65, 95% CI 0.47–0.90). Conclusions: Over two decades, in medically managed NSTE-ACS patients, short term prognosis has significantly improved while 1-year mortality demonstrated improvement only recently, likely due to incremental benefits of medical management. Further studies are needed to examine treatment modalities in these unique ACS patients. FUNDunding Acknowledgement: Type of funding sources: None.